LEGAL PROTECTION FOR CONSUMERS AGAINST TRADE THAT DOES NOT FOLLOW HALAL PRODUCTION - Yeti Kurniati (Sean Institute, 2022)
Food is a food product that is widely and freely circulated in the community, food that will be consumed so as not to harm consumers must provide adequate, correct, honest and responsible information. Over time, there have been many violations committed by business actors related to food circulating in the market and it is very risky when consumed by consumers. In food trading activities, it shows that there are still many business actors who sell dangerous food products, this can be detrimental to consumers because it can endanger the health and safety of consumers. The purpose of this study is to determine legal protection for consumers against trading that does not follow halal production in terms of Law Number 8 of 1999 concerning Consumer Protection. Meanwhile, the method used in this study is descriptive analytical method with a normative juridical approach. Data, namely secondary data collected by way of literature study or document study, then analysed qualitatively normative. Based on the results of the research that the consumer's position is strictly regulated in Law Number 8 of 1999 concerning Consumer Protection. In article 1, paragraph 1, it is explained that consumer protection is all efforts that guarantee legal certainty to provide protection to consumers in order to protect consumer rights so that consumers do not suffer losses committed by business actors, especially in the formalin food sector, These regulations are useful for consumers to know the limits or requirements for good food and what actions are prohibited by business actors.